Higher cardiorespiratory fitness levels are associated with greater hippocampal volume in breast cancer survivors - Chaddock-Heyman, Laura; Mackenzie, Michael J.; Zuniga, Krystle; Cooke, Gillian E.; Awick, Elizabeth; Roberts, Sarah; Erickson, Kirk I.; McAuley, Edward; Kramer, Arthur F. (Frontiers in Human Neuroscience, 2015)
As breast cancer treatment is associated with declines in brain and cognitive health, it is important to identify strategies to enhance the cognitive vitality of cancer survivors. In particular, the hippocampus is known to play an important role in brain and memory declines following cancer treatment. The hippocampus is also known for its plasticity and positive association with cardiorespiratory fitness. The present study explores whether cardiorespiratory fitness may hold promise for lessening declines in brain and cognitive health of a sample of breast cancer survivors within three years of completion of primary cancer treatment. We explored the role of cardiovascular fitness in hippocampal structure in breast cancer survivors and non-cancer female controls, as well as performed a median split to compare differences in hippocampal volume in relatively higher fit and lower fit cancer survivors and non-cancer controls. Indeed, cardiorespiratory fitness and total hippocampal volume were positively correlated in the cancer survivors. In particular, higher fit breast cancer survivors had comparable hippocampal volumes to non-cancer control participants (Cohen’s d=0.13) (p>0.3), whereas lower fit breast cancer survivors showed significantly smaller hippocampal volumes compared to both lower fit and higher fit control participants (Cohen’s d=0.87, p<0.05). These results are the first to identify that cardiorespiratory fitness may protect the brain health of breast cancer survivors within three years of treatment. The present study uniquely contributes to the field of cancer and cognition and emphasizes the importance of investigating how individual differences in cardiorespiratory fitness play a role in brain changes of breast cancer survivors.